2019
DOI: 10.1002/jso.25446
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a nine‐gene panel as a prognostic indicator for recurrence with muscle‐invasive bladder cancer

Abstract: Background and Objectives Bladder cancer is one of the most common and highly recurrent cancers worldwide. Recurrence‐associated genes may potentially predict cancer recurrence. We aimed to construct a recurrence‐associated gene panel to improve the prognostic prediction of bladder cancer. Methods Based on DNA sequencing and clinical data from the TCGA‐BLCA project, we identified 10 potential driver genes significantly associated with recurrence of bladder cancer. We performed multivariable logistic regression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 48 publications
1
23
0
Order By: Relevance
“…Next, targetscan website was employed to predict target gene of miR-490-3p. In numerous putative targets of miR-490-3p, POU3F2 was selected due to a crucial pro-tumor effect in numerous cancers [25,26]. The 3′UTR of POU3F2 (Fig.…”
Section: Pou3f2 As a Target Of Mir-490-3p Was Overexpressed In Hcc mentioning
confidence: 99%
“…Next, targetscan website was employed to predict target gene of miR-490-3p. In numerous putative targets of miR-490-3p, POU3F2 was selected due to a crucial pro-tumor effect in numerous cancers [25,26]. The 3′UTR of POU3F2 (Fig.…”
Section: Pou3f2 As a Target Of Mir-490-3p Was Overexpressed In Hcc mentioning
confidence: 99%
“…MIBCs have a more diverse mutation spectrum [25,26] and display high overall mutation rates similar to those of non-small cell lung cancers and melanoma [27]. MIBCs is also highly recurrent cancers worldwide [28] .…”
Section: Discussionmentioning
confidence: 99%
“…32 In addition, a nine-gene panel that included METTL3 was identified as a prognostic indicator for the recurrence of muscle invasive bladder cancer. 33 Yang et al 34 showed that METTL3 and ALKBH5 regulated m 6 A modification of the 3′-UTR of the oncogene CDCP1 mRNA and that YTHDF1 recognized m 6 A modification to promote CDCP1 translation in bladder cancer. Similarly, Jin et al 35 found that METTL3 and ALKBH5 regulated the m 6 A modification of the 3′-UTR of the oncogene ITGA6 mRNA and that YTHDF1/3 recognized m 6 A modification to promote ITGA6 translation in bladder cancer.…”
Section: Bladder Cancermentioning
confidence: 99%